Tetrodotoxin and the state-of-the-art progress of its associated analytical methods - Mi, Wei; Liu, Sha (Frontiers in Microbiology, 2024)
Tetrodotoxin (TTX), which is found in various marine organisms, including pufferfish, shellfish, shrimp, crab, marine gastropods, and gobies, is an effective marine toxin and the cause of many seafood poisoning incidents. Owing to its toxicity and threat to public health, the development of simple, rapid, and efficient analytical methods to detect TTX in various food matrices has garnered increasing interest worldwide. Herein, we reviewed the structure and properties, origin and sources, toxicity and poisoning, and relevant legislative measures of TTX. Additionally, we have mainly reviewed the state-of-the-art progress of analytical methods for TTX detection in the past five years, such as bioassays, immunoassays, instrumental analysis, and biosensors, and summarized their advantages and limitations. Furthermore, this review provides an in-depth discussion of the most advanced biosensors, including cell-based biosensors, immunosensors, and aptasensors. Overall, this study provides useful insights into the future development and wide application of biosensors for TTX detection.